2007
DOI: 10.3748/wjg.v13.i3.403
|View full text |Cite
|
Sign up to set email alerts
|

Environmental noise alters gastric myoelectrical activity: Effect of age

Abstract: AIM:To evaluate the effect of age and acoustic stress on gastric myoelectrical activity (GMA) and autonomic nervous system function. METHODS:Twenty-one male subjects (age range 22-71 years, mean 44 years) were recruited and exposed, in random order, to three auditory stimuli (Hospital noise, conversation babble and traffic noise) after a 20-min baseline. All periods lasted 20 min and were interspersed with a 10 min of recovery. GMA was obtained using a Synectics Microdigitrapper. Autonomic nerve function was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…EOL environments contain many potential sources of noise, including machines and equipment, residents’ verbal agitation, and staff conversations (80, 69, 90). In general contexts, excess noise has been linked to adverse physiological and psychological consequences, including elevated blood pressure (86), sleep loss (88), decreased gastric motility in older subjects (87), reduced social interaction (85), and increased aggression and disruptive behavior (83). In 29 in-patient wards in a Korean hospital, 103 patients experienced sleep disturbance (as measured by the Pittsburgh Sleep Quality Index) that was significantly correlated to noise level (as measured by noise dosimeters) (88).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EOL environments contain many potential sources of noise, including machines and equipment, residents’ verbal agitation, and staff conversations (80, 69, 90). In general contexts, excess noise has been linked to adverse physiological and psychological consequences, including elevated blood pressure (86), sleep loss (88), decreased gastric motility in older subjects (87), reduced social interaction (85), and increased aggression and disruptive behavior (83). In 29 in-patient wards in a Korean hospital, 103 patients experienced sleep disturbance (as measured by the Pittsburgh Sleep Quality Index) that was significantly correlated to noise level (as measured by noise dosimeters) (88).…”
Section: Resultsmentioning
confidence: 99%
“…In 29 in-patient wards in a Korean hospital, 103 patients experienced sleep disturbance (as measured by the Pittsburgh Sleep Quality Index) that was significantly correlated to noise level (as measured by noise dosimeters) (88). Separately, in a randomized controlled trial, 21 male subjects between the ages of 22 and 71 underwent three auditory interventions, and older subjects displayed lower gastric myoelectric activity compared to younger subjects (87).…”
Section: Resultsmentioning
confidence: 99%
“…2 Noise stress has been linked to a variety of health issues including cardiovascular diseases, 3 mental illness, 4 sleep disorder 5 and hypertension. 6 Furthermore, gastrointestinal motility disorder (GIMD), gastritis and peptic ulcers 7,8 have been noticed in populations who are exposed to high levels of noise. However, little is known about prevention and treatment of noise on GIMD and gastric stress ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological noise studies when focused on mean blood pressure found that there is sufficient evidence that noise, especially aircraft noise, increases the risk of hypertension in adults (Babisch and Kamp, 2009). Other effects of high noise levels were increased frequency of headaches (Martin et al, 2005), vertigo (Tzaneva et al, 2000), and stomach ulcers (Castle et al, 2007).…”
Section: Discussionmentioning
confidence: 99%